2012
DOI: 10.1080/03098265.2011.576754
|View full text |Cite
|
Sign up to set email alerts
|

Student-Produced Podcasts as an Assessment Tool: An Example from Geomorphology

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
(33 reference statements)
6
28
0
1
Order By: Relevance
“…HMI 1992) has been transformed into an enjoyable, engaging, fun means of learning in the approach adopted here (see Figure 2; Table 2, rank #3). Kemp et al (2012) suggest that a similar approach incorporating podcasting into fieldwork was also enjoyed by students and motivated students in their study. The spin--off to such enjoyable learning is that digital video assessment has improved levels of understanding of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HMI 1992) has been transformed into an enjoyable, engaging, fun means of learning in the approach adopted here (see Figure 2; Table 2, rank #3). Kemp et al (2012) suggest that a similar approach incorporating podcasting into fieldwork was also enjoyed by students and motivated students in their study. The spin--off to such enjoyable learning is that digital video assessment has improved levels of understanding of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Kemp et al, 2012), has been deemed to be successful in engaging students at a more advanced level in physical geography fieldwork. Jarvis & Dickie (2010) and Kemp et al (2012) review a range of uses for similar podcasts in student learning, among which is the suggestion that they provoke reflective thought (Fisher & Baird, 2006), which in turn fosters deeper levels of learning and engagement (Jarvis & Dickie, 2010;Kemp et al, 2012). Mavroudi & Jöns (2011) also recognised similar benefits of incorporating video documentaries into their assessment of human geography fieldwork and concluded that "video documentary works extremely well to stimulate students' interest and critical thinking" p.18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, it could indeed be argued that this form of assessment might have a broader relevance beyond distance learning institutions (Armstrong et al, 2009;Kemp et al, 2012;Lee et al, 2008;Pegrum et al, 2015).…”
Section: Personal Engagement Authenticity and Relevancementioning
confidence: 99%
“…Fieldwork is an integral component of a wide range of Bioscience, Geography, Earth and Environmental Science undergraduate programmes. Student reflection and engagement during fieldwork can be promoted through the integration of technology into the learning activities (Fisher & Baird, 2006;Jarvis & Dickie, 2010;Mavroudi & Jöns, 2011;France & Wakefield, 2011;Kemp et al, 2012;Dando & Chadwick, 2014 and Fuller & France, this volume). The use of mobile technologies in the field is perceived to enhance fieldwork learning through improved speed, ease and immediacy of data collection, sharing, analysis and presentation (Welsh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%